(untitled) (Italian Journal of Public Health, 2009)
Background: The improvement of management in healthcare system is one of the basic goals of the modern management style of Serbia. Among the most significant institutions of public healthcare is the Institute of Public Health, which has a long tradition within the country. Methods: This cross-sectional study was conducted from December 2007 to January 2008 at the Institution of Public Health (IPH) in Kikinda. The study involved a population from the North Banat district, who, at the time, used some of the Institution’s services: hygienic-ecological, epidemiological, and microbiological. The instrument of the study was a questionnaire which was used to assess the opinion of the users of the Institution’s services in terms of the performance and the quality of the services provided. Results: The relation between political factors in the country and the public health services provided was highly assessed by the responders, with the highest influence being attributed to the changes in the government, i.e. state elections, and the lowest to the local authorities. The responders were satisfied with the quality of the provided services but satisfaction regarding the collaboration between the IPH and various regional organizations was lower. The social factors, population aging and multicultural environment, were evaluated as being the most significant for the performance of the IPH. Conclusions: The identification of population needs and requirements for active inclusion in resolving priority problems should incorporate in the strategic management of public healthcare institutions, which would lead to the achievement of defined goals, as well as to the improved satisfaction of the users.